The problem of the methodological understanding of the new role of Russia: reasons, prospects, risks - Gigin, Vadim F. (Journal of the Belarusian State University. Philosophy and Psychology, 2019)
The article deals with the prerequisites for the formation of a new geopolitical role of Russia. The author makes an attempt to develop a methodology for the analysis of the process as a phase transition of the world order from a unipolar to a multipolar world. The definition of the Putin doctrine as the strategy of Russia’s actions in the world. Also, the author analyzes the strengths and weaknesses of this strategy.